International students’ direct and parasocial contact, and attitude towards Malaysian host nationals: the mediating roles of cultural identification and Islamic identity - Tengku Mohd Azzman, Tengku Siti Aisha; A. Manaf, Aini Maznina; Sedu, Nerawi (IIUM Press, 2025)
International students may find it challenging to adjust to a new environment. Based on the principles of intergroup contact, this study explored factors that influenced attitude towards Malaysian host nationals. Communication quality (CQ), parasocial interaction (PSI), cultural identification (CID), and Islamic identity (IID) is predicted to influence attitude towards Malaysian host nationals (ATT). It is also hypothesized that CID and IID will function as mediators. Eight hypotheses were proposed to test these relationships. A questionnaire was distributed online in 2024 among international students in Malaysia (N = 253). The Hayes PROCESS macro was used to test the parallel mediation analyses (model 4). CID and CQI had a significant positive direct effect on ATT. CID also mediated the relationship between PSI and ATT, and between CQ and ATT. However, IID is not a significant mediator. The repercussion of these findings on intergroup contact and acculturation of international students were also deliberated.